FEASIBILITY STUDY WITH BUSINESS METHODS CANVAS MODELS (CASE STUDY OF AYU SEMINYAK VILLA) - Kadek Indra Lesmana; Ni Wayan Ari Sudiartini; Ni Putu Yuli Tresna Dewi (Nusantara Hasana Journal, 2023)
Villa is a place that is usually used to stay or spend the night by offering a beautiful natural view and tranquility for its residents. Generally, villa rentals are booming when entering weekends or during long holidays. In addition, the lack of financial planning in carrying out their business causes irregular business finances, so that in making business decisions they often face doubts. Villa Ayu Seminyak as a provider of accommodation accommodation in the Bali area which aims to help consumers find it easy to get lodging accommodations. This study aims to determine and analyze the business feasibility of Villa Ayu Seminyak in terms of the business canvas and SWOT analysis. The feasibility analysis uses Canva business analysis and SWOT analysis The analysis used in this study is a qualitative data analysis technique, the data obtained through literature, interviews and documentation conducted at Villa Ayu Seminyak. The results of the study show that from the aspects and analysis carried out at the Villa Ayu Seminyak company, it has met the business criteria and is feasible to run. This research is useful as information on Villa Ayu Seminyak's efforts to improve the quality of the company in a sustainable manner.